Where are the dedicated scholars of management learning and education?. Issue 2 (April 2016) - Arbaugh, JB
The vibrancy of a field is predicated on the attraction and sustained efforts of increasing numbers of dedicated scholars. However, in management education research, historically this level of dedicated research appears to have been entrusted to a hearty relative few. In this essay, I examine some commonly presented objections to focusing one's research attention on issues of the scholarship of teaching and learning in the management realm. Then, I present counterarguments that, although at one time may have been legitimate concerns, increasingly are unfounded. I transition to arguing that some scholars having a dedicated emphasis on management education research is a good, and perhaps even necessary, thing as management education becomes more global. I conclude my discussion by noting pressing opportunities and need areas for further accelerating the development of new management education scholars.